Recent Progress of Metal Carbides Encapsulated in Carbon‐Based Materials for Electrocatalysis of Oxygen Reduction Reaction. Issue 1 (18th November 2019) - Yan, Xiang‐Hui; Prabhu, P.; Xu, Hao; Meng, Ziwei; Xue, Tong; Lee, Jong‐Min
Abstract: Fuel cells represent the most suitable energy conversion, capable of addressing energy crises and environmental pollution. Recently, as one of nonprecious metal catalysts (NPMCs), the MC@N‐C (M = Fe, Co, Ni, Mo, W) catalysts, especially for Fe3 C encased in carbon layer (denoted as Fe3 C@N‐C) have emerged as promising replacements for costly Pt‐based catalysts for oxygen reduction reaction (ORR). This review highlights the synthetic strategies undertaken such as hard template, soft template, and template‐free methods for deriving enhancements in electrocatalytic activity and durability. It also provides a comparison on the synthetic methods and catalytic performance and points out issues in the ORR measurements and activity comparison. In addition, understanding of the proposed active sites and corresponding mechanisms for ORR are covered. The recent advances shed light on contributions of morphology, hierarchical pore structures, density and dispersion of active sites, and synergistic effects of multiple active sites, which endow Fe3 C@N‐C electrocatalysts with enhanced ORR performance. These interesting effects are attained as a result of increased exposure and accessibility of the active sites to O2 molecules, faster charge and mass transfer, and finally, protection of active sites by carbon shells. Finally, the challenges and perspectives to further improve performance of Fe3 C@N‐C are discussed. Abstract : This review mainly focuses on the synthetic strategies, electrocatalytic performances and corresponding reaction mechanisms of the metal carbides encapsulated in nitrogen‐doped carbon materials (MC@N‐C, M = Fe, Co, Ni, Mo, W), especially for the Fe3 C@N‐C catalysts toward oxygen reduction reaction (ORR). The key factors of affecting ORR and some issues in the measurements and activity evaluation are discussed and highlighted.